Uncommon vascular access in patients who need hemodialysis - Emma Esther González García; Yulior Gé Pablo Martínez; Reynaldo Pedro Rodríguez Beyris (Centro Provincial de Información de Ciencias Médicas, 2016)
The case reports of 2 patients with chronic terminal renal failure who had no conventional venous accesses and loss of the peritoneum function are presented; therefore, they didn't have clinical conditions for a renal transplant. The possibility of vascular access was studied and after several failed attempts for hemodialysis fistula, it was possible to continue with the purifying therapy and a catheter was implanted in the external iliac vein by means of the Gibson technique, which determined the continuity of hemodialysis with lengthening of their lives.